2002
DOI: 10.1038/419359a
|View full text |Cite|
|
Sign up to set email alerts
|

Visual structure of a Japanese Zen garden

Abstract: The dry landscape garden at Ryoanji Temple in Kyoto, Japan, a UNESCO world heritage site, intrigues hundreds of thousands of visitors every year with its abstract, sparse and seemingly random composition of rocks and moss on an otherwise empty rectangle of raked gravel. Here we apply a model of shape analysis in early visual processing to show that the 'empty' space of the garden is implicitly structured and critically aligned with the temple's architecture. We propose that this invisible design creates the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…After such alterations, medial axes of the garden lack a consistent branching rule and in most cases do not even approximately resemble a tree structure (supplementary material, Van Tonder et al 2002). The structure defined by the shape of the ground in the original layout of Ryoanji is nonaccidental.…”
Section: Analysis Of the Structure Of Visual Ground In A Japanese Rocmentioning
confidence: 99%
See 1 more Smart Citation
“…After such alterations, medial axes of the garden lack a consistent branching rule and in most cases do not even approximately resemble a tree structure (supplementary material, Van Tonder et al 2002). The structure defined by the shape of the ground in the original layout of Ryoanji is nonaccidental.…”
Section: Analysis Of the Structure Of Visual Ground In A Japanese Rocmentioning
confidence: 99%
“…It could therefore be an appropriate method to analyze minimalist designs often encountered in Japanese dry landscape gardens. A summary of our previous work on structural analysis of the Ryoanji dry rock garden (Van Tonder et al 2002) is presented here.…”
Section: Analysis Of the Structure Of Visual Ground In A Japanese Rocmentioning
confidence: 99%
“…The importance of symmetry in architecture and landscape design is well known and has been carefully observed since the first century BCE, as demonstrated in the classical architectural writer Vitruvius' thesis [1] writing in circa 15 BCE, to modern days [2]. It is also a defining factor in a well-designed Zen garden [3]. In addition, numerous studies have shown that a symmetric face or body (for a review, see [4][5][6]) is more attractive than an asymmetric one.…”
Section: Introductionmentioning
confidence: 99%
“…Kanizsa's analysis, for example, has provided excellent bases on which to determine neurophysiological correlates of amodal contours (Baumgartner, von der Heydt, & Peterhans, 1984;De Weerd, Desimone, & Underleider, 1998) while the Gestalt principle of Figure/Ground segregation has been important in the neuronal analysis of transparency phenomena (Qiu & von der Heydt, 2005. Similarly, work on the perceptual significance of medial axis representations (Bouix, Siddiqui, Tannenbaum, & Zucker, 2006;Leyton, 1987Leyton, , 1992van Tonder, Lyons, & Ejima, 2002) suggests yet another avenue for neurophysiologic investigation. The problem arises mostly from the assumptions that guide the different options and/or from absolutist approaches to the data by the methodology adopted to explain and interpret the phenomenon.…”
mentioning
confidence: 99%